2023
DOI: 10.1038/s42003-023-05013-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular evidence for the impact of a hypertrophic cardiomyopathy-associated RAF1 variant on the structure and function of contractile machinery in bioartificial cardiac tissues

Abstract: Noonan syndrome (NS), the most common among RASopathies, is caused by germline variants in genes encoding components of the RAS-MAPK pathway. Distinct variants, including the recurrent Ser257Leu substitution in RAF1, are associated with severe hypertrophic cardiomyopathy (HCM). Here, we investigated the elusive mechanistic link between NS-associated RAF1S257L and HCM using three-dimensional cardiac bodies and bioartificial cardiac tissues generated from patient-derived induced pluripotent stem cells (iPSCs) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…The alpha-isoform of PKC directly activates RAF1 [ 281 ], providing evidence for a complex link between the signaling pathway downstream of growth factor receptors in the context of cardiac hypertrophy. Others have reported that GPCR signaling can be linked directly to RAS GTPase ( Figure 2 ) [ 282 ], and GTP-bound RAS interacts with many downstream effectors which in turn transmit the signal for activating multiple signaling pathways [ 283 , 284 ], potentially promoting hypertrophic responses in cardiomyocytes. Additionally, others reported that the C-terminus of the AT1 receptor associates with JAK2 upon binding of the ligand, resulting in JAK2/STAT3 pathway activation [ 285 , 286 ], indicating another example of the crosstalk of signaling pathways in response to hypertrophy-associated stress signals.…”
Section: Mediators Of Cardiac Remodelingmentioning
confidence: 99%
“…The alpha-isoform of PKC directly activates RAF1 [ 281 ], providing evidence for a complex link between the signaling pathway downstream of growth factor receptors in the context of cardiac hypertrophy. Others have reported that GPCR signaling can be linked directly to RAS GTPase ( Figure 2 ) [ 282 ], and GTP-bound RAS interacts with many downstream effectors which in turn transmit the signal for activating multiple signaling pathways [ 283 , 284 ], potentially promoting hypertrophic responses in cardiomyocytes. Additionally, others reported that the C-terminus of the AT1 receptor associates with JAK2 upon binding of the ligand, resulting in JAK2/STAT3 pathway activation [ 285 , 286 ], indicating another example of the crosstalk of signaling pathways in response to hypertrophy-associated stress signals.…”
Section: Mediators Of Cardiac Remodelingmentioning
confidence: 99%
“…The MAPK signaling pathway plays a critical role in the regulation of various cellular processes such as differentiation, survival, and, in particular, proliferation ( Zhang & Liu, 2002 ; Guo et al, 2020 ; Ullah et al, 2022 ). Dysregulation of this pathway is frequently associated with the initiation and progression of human diseases, including cancer ( Degirmenci et al, 2020 ) and developmental disorders such as RASopathies ( Dar & Brady, 2022 ), the latter exemplified by the RAF1 S257L mutation causing cardiomyopathy ( Dhandapany et al, 2014 ; Jaffre et al, 2019 ; Nakhaei-Rad et al, 2023a ). As a key component of the MAPK pathway, C-RAF is activated by upstream receptor–RAS signaling and subsequently activates several downstream effectors, particularly MEK1/2 kinases and subsequently ERK1/2 signaling ( Wimmer & Baccarini, 2010 ; Matallanas et al, 2011 ; Ullah et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jaffre et al, 2019;Nakhaei-Rad et al, 2023a). As a key component of the MAPK pathway, C-RAF is activated by upstream receptor-RAS signaling and subsequently activates several downstream effectors, particularly MEK1/2 kinases and subsequently ERK1/2 signaling(Wimmer & Baccarini, 2010;Matallanas et al, 2011;Ullah et al, 2022).…”
mentioning
confidence: 99%
“…The MAPK signaling pathway plays a crucial role in regulating various cellular processes such as differentiation, survival, and in particular proliferation (56)(57)(58). Dysregulation of this pathway is often associated with the development and progression of human diseases, including cancer (4) and developmental disorders like RASopathies (59), the latter exemplified by the RAF1 S257L mutation causing cardiomyopathy (60)(61)(62). As a key component of the MAPK pathway, C-RAF is activated by upstream receptor-RAS signaling and subsequently activates various downstream effectors, particularly MEK1/2 kinases and thus ERK1/2 signaling (21,22,57).…”
Section: Discussionmentioning
confidence: 99%